Dancing with pharmaceutical industry – medical practice between ethics and business - CRĂCIUNAŞ, Sorin C.; CRĂCIUNAŞ, Diana V. (Annals of Spiru Haret University. Economic Series, 2010)
The relation between physicians and the pharmaceutical companies has been increasingly discretted issue over the last several years. Moreover, such relations have been proven to influence the prescribing patterns to stimulate drug supplying within hospitals, to encourage publications and research articles and even to contribute to critical article non-publication. There is a complex relation between physicians, medical organizations and academic departments, on the one hand and industry on the other. Therefore, industry makes its living from the physicians prescriptions and from the devices and services they purchase. Yet physicians, medical organizations, and academic departments commonly receive money and other benefits from the industry. This paper reviews specialist literature and addresses the real dimension of the physician-health related industry worldwide interaction. Unfortunately, Romania has not provided any data yet, because this issue has not been officially analyzed in our country.